(untitled) (Scientific journal of the Fergana State University, 2022)
The article deals with the use of gravel-sand mixtures for highways treated with cement with the addition of bitumen emulsion. Experimental studies (tests) were carried out as part of a study justifying the effectiveness of strengthening the base with the help of complex binders. This article presents tests carried out in several formulations with the study of construction methods and physical and mechanical properties of materials (cement, gravel-sand mixture and bitumen emulsion). The test results showed a decrease in water absorption when using gravel-sand mixtures treated with cement with the addition of bitumen emulsion, which increases the strength of the structure.